P86 COVID-19 history reported by men who have sex with men (MSM) in the UK in a large, community survey ('RiiSH-COVID'). (16th June 2022) - Ogaz, Dana; Allen, Hester; Reid, David; Brown, Jack; Mohammed, Hamish; Saunders, John; Hughes, Gwenda; Mercer, Catherine
Abstract : Introduction: As COVID-19 has deepened health inequalities, we examine the COVID-19 experience of MSM as a population disproportionately affected by poor-health. Methods: An online cross-sectional survey of MSM recruited via social media and dating applications for 3 weeks in November/December 2021. Questions included those on COVID-19 experience addressing: COVID-19 test history; when (if ever) tested positive; self-perception of ever having had COVID-19 and long-COVID. Logistic regression was used to assess sociodemographic and behavioural characteristics associated with these outcomes. Results: Among 1, 038 participants (median age: 41; 88.1% white ethnicity): most reported ever testing for COVID-19 (95.0%; n=987), while 19.6% (193/987) reported a positive result [8.1% (80/987) testing positive since August 2021]. In those without a prior positive test (n=793) or testing history (n=52), an additional 148 participants reported self-perceived COVID, resulting in 32.8% (341/1038) with a COVID-19 history. In these, one-quarter (25.2%; 86/341) reported long-COVID (8.3%; 86/1038 of all) and 4.1% (14/341) hospitalisation history for COVID-related symptoms (1.8%; 19/1038 of all). COVID-19 history was associated with residence in England (aOR:1.52, 95%CI:1.02-2.28), degree-level education (aOR:1.33;95%CI:1.01-1.75), and vaccination status (aOR:2.98, 95%CI:1.61-5.53, none/one dose vs. boosted). Long-COVID was associated with hospitalisation history (aOR:3.21;95%CI:1.09-9.45) and degree-level education (aOR:0.56;95%CI:0.36-0.99). Conclusion: In this large community sample, one in five MSM reported testing positive for COVID-19, and one-third had a COVID-19 history. There was no evidence of age or ethnicity-related inequalities, although long-COVID appears to exceed general population estimates. Continued monitoring of long-COVID in MSM is warranted as COVID-19 infections in the UK continue to increase.